Wright’s Paul and the cloud of (other) witnesses - Bockmuehl, M (Pennsylvania State University Press, 2014)
With appreciation for Wright's admirable achievement, this article takes its starting point from a "word cloud" of Paul and the Faithfulness of God in order to illustrate this work's emphases as well as possible lacunae. Relative silence envelops questions such as (1) Paul's biography and its theological or mimetic value, including Luke's Paul in Acts; (2) criticisms of Wright's customarily straightforward equation of Paul's preferred term Christ with Messiah; (3) the hermeneutical implications for this project of any "deutero-Pauline" or indeed strictly "pseudonymous" authorship; (4) the place of observant Jews in "all Israel." Wright's is a Paul of soteriological logos rather than of "Christomimetic" ethos, of suffering or of sacrifice. But these are queries for constructive engagement with what is now the most complete account of its kind in existence.